2013
DOI: 10.1021/bc4001799
|View full text |Cite
|
Sign up to set email alerts
|

Clickable Tyrosine Binding Bifunctional Linkers for Preparation of DNA–Protein Conjugates

Abstract: We have prepared bifunctional linkers containing clickable functional groups that enable preparation of protein-DNA conjugates through binding onto tyrosine residues. Mild conjugation strategy was demonstrated using two proteins, streptavidin(STV) and myoglobin (Mb) and it resulted in conjugates with preserved functionality of both the proteins and DNA strands. Furthermore, we show that protein-DNA conjugates can be successfully immobilized onto solid surface containing complementary DNA strands and the enzyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 39 publications
5
55
0
Order By: Relevance
“…TAD functionalization was also recently used to radiolabel tyrosine of natural proteins using [18F]4‐(4‐fluorophenyl)‐1,2,4‐triazole‐3,5‐dione . In another example, Bauer et al prepared bifunctional TAD linkers and showed protein–DNA conjugation …”
Section: Introductionmentioning
confidence: 99%
“…TAD functionalization was also recently used to radiolabel tyrosine of natural proteins using [18F]4‐(4‐fluorophenyl)‐1,2,4‐triazole‐3,5‐dione . In another example, Bauer et al prepared bifunctional TAD linkers and showed protein–DNA conjugation …”
Section: Introductionmentioning
confidence: 99%
“…20,21 Intrigued by these results, we studied D1 modication with cyclic diazodicarboxamides 4-phenyl-3H-1,2,4-triazole-3,5(4H)-dione (PTAD) in mixed organic/aqueous media (Scheme 3). 22 Therefore, it is expected to construct advanced biomaterials with tyrosine-conjugated biodynamer as the building block through the tyrosine-click reaction. of PTAD for 24 h. Aer purication by dialysis, 1 H NMR analysis revealed the presence of the signals of acylhydrazone proton (CH]NNH) and aromatic -OH, and the appearance of signals at d 11.3, 7.42, 7.25 ppm corresponding to the modied PTAD moiety (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…9 Tyrosine residues have unique reactivity because of the acidic proton of the phenol ring. [20][21][22] Intrigued by the possibility of using ideas from the protein modication through tyrosine, we sought to introduce tyrosine moiety into the polymer to create a facile bioconjugation strategy for the synthetic polymers through tyrosine. Under acidic conditions, an ene-like reaction occurs at a carbon atom on the aromatic ring.…”
Section: Introductionmentioning
confidence: 99%
“…This makes engineering a single, non‐perturbative reactive site in a protein of interest relatively straightforward . The use of diazocarboxamides for tyrosine‐phenol targeting has also been reported as an efficient means to conjugate DNA to proteins (Figure c); however, this approach has not been widely adopted, likely because it still requires the user to synthesize diazocarboxamide‐containing heterobifunctional linkers . Another promising strategy for targeting a single site in proteins is N‐terminal (α‐amine) protein labeling via 2‐pyridinecarboxyaldehydes as initially reported by the Francis lab .…”
Section: Bioorthogonal Chemistry For Dna Barcoding Of Proteins and Otmentioning
confidence: 99%